Six-month neurological and psychiatric outcomes in 236,379 survivors of COVID-19 - Taquet, M; Geddes, JR; Husain, M; Luciano, S; Harrison, PJ (Elsevier, 2021)
Background: Neurological and psychiatric sequelae of COVID-19 have been reported, but more data are needed to adequately assess the effects of COVID-19 on brain health. We aimed to provide robust estimates of incidence rates and relative risks of neurological and psychiatric diagnoses in patients in the 6 months following a COVID-19 diagnosis.